2015
DOI: 10.1039/c5ra01180a
|View full text |Cite
|
Sign up to set email alerts
|

Fast and low-temperature synthesis of one-dimensional (1D) single-crystalline SbSI microrod for high performance photodetector

Abstract: A new rapid and low temperature hydrothermal process has been developed to synthesize one-dimensional (1D) single-crystalline SbSI microrods at 160 C for 4 h with high quality. Moreover, a first individual SbSI microrod based photodetector equipped with indium-tinoxide (ITO) electrodes is constructed on a SiO 2 /Si substrate. The resulting device displays a remarkable response to visible light with an on-off ratio up to 727, a detectivity of 2.3 Â 10 8 Jones, a noise equivalent power of 1.7 Â 10 À10 W/Hz 1/2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(85 citation statements)
references
References 34 publications
4
80
1
Order By: Relevance
“…However, a large number of defects in polycrystalline films limit the device performances. Alternatively, perovskite single crystals are expected to achieve impressive photosensing performances due to their absence of grain boundaries, low trap densities, and large carrier mobilities . Apart from polycrystalline film and single crystal, low‐dimensional perovskite nanostructures including 1D nanowire and 2D nanosheet have been successfully synthesized and received increasing research attention, primarily for their fascinating optical and electronic properties resulting from the quantum‐size effects .…”
Section: Various Perovskite Structures For Photodetectorsmentioning
confidence: 99%
“…However, a large number of defects in polycrystalline films limit the device performances. Alternatively, perovskite single crystals are expected to achieve impressive photosensing performances due to their absence of grain boundaries, low trap densities, and large carrier mobilities . Apart from polycrystalline film and single crystal, low‐dimensional perovskite nanostructures including 1D nanowire and 2D nanosheet have been successfully synthesized and received increasing research attention, primarily for their fascinating optical and electronic properties resulting from the quantum‐size effects .…”
Section: Various Perovskite Structures For Photodetectorsmentioning
confidence: 99%
“…Surthi et al have reported an integrated structure of a semiconducting La–Ca–Mn–oxide and SbSI, which was used as a ferroelectric memory element. Chen et al have reported an individual SbSI photodetector using SbSI microrods. Theoretical calculations revealed a high charge mobility for SbSI, related to the low effective masses of the charge carriers; hence, SbSI demonstrates promise for photovoltaic applications .…”
Section: Performance Of the Sbsi‐based Solar Cells Prepared By Using mentioning
confidence: 99%
“…The SbSI is easy to grow into one-dimensional rods or urchin-like structures, [22][23][24][25]32 even from a continuous thin film. 22 Therefore, to apply these discontinuous SbSI films into planar optoelectronic devices, an insulating polymer such as poly(methyl methacrylate) 22,27 should be integrated into such films to minimize leakage currents caused by the presence of inevitable voids in the SbSI layer.…”
Section: -6mentioning
confidence: 99%
“…bandgap (E g ) close to 1.8 eV. 9,21,22 Finally, SbSI can be applied in various capacities, including as a photodetector, 22,23 photocatalyst, 24 humidity sensor, 25 thermoelectric device, 26 and self-powered optoelectronic device, 27 in addition to its use in solar cells. This broad range of applications can be further extended to include room-temperature radiation detection and p-type transparent conduction by substituting Bi for Sb.…”
mentioning
confidence: 99%